2021
DOI: 10.14488/bjopm.2021.029
|View full text |Cite
|
Sign up to set email alerts
|

Mediating role of strategic orientations in the relationship between entrepreneurial orientation and performance of Saudi SMEs

Abstract: Goal: This study aims to examine the mediating role of strategic orientations in the relationship between entrepreneurial orientation and performance of small and medium enterprises (SMEs) in Saudi Arabia. Design/Methodology/Approach: Quantitative analysis techniques is used in this study. Data from 206 KSA owners / managers of SMEs is obtained and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). Results: Findings indicate that strategic orientations mediate the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 75 publications
(102 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, absorptive capacity moderated the correlation between entrepreneurial orientation and project management success, and this correlation became larger and more powerful with the mere existence of absorptive capacity. Abdulrab et al (2021) explored the influence of strategic orientations in mediating the correlation between entrepreneurial orientation and efficient implementation in Saudi SMEs. The research findings revealed that KSA SME management teams should maintain an intense focus on entrepreneurial behavior and develop a unique business strategy approach to achieve overall effectiveness.…”
Section: Recent Research Findings On Entrepreneurial Orientation and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, absorptive capacity moderated the correlation between entrepreneurial orientation and project management success, and this correlation became larger and more powerful with the mere existence of absorptive capacity. Abdulrab et al (2021) explored the influence of strategic orientations in mediating the correlation between entrepreneurial orientation and efficient implementation in Saudi SMEs. The research findings revealed that KSA SME management teams should maintain an intense focus on entrepreneurial behavior and develop a unique business strategy approach to achieve overall effectiveness.…”
Section: Recent Research Findings On Entrepreneurial Orientation and ...mentioning
confidence: 99%
“… Abdulrab et al (2021) explored the influence of strategic orientations in mediating the correlation between entrepreneurial orientation and efficient implementation in Saudi SMEs. The research findings revealed that KSA SME management teams should maintain an intense focus on entrepreneurial behavior and develop a unique business strategy approach to achieve overall effectiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The conceptual framework provides detailed information on the interconnections between the different variables in the conceptual framework (Hair et al, 2010;Ho, 2006;Abdulrab et al, 2021;Abdulrab et al, 2022;Al-Mamary et al, 2020;Al-Ghurbani et al, 2022;Al-Mamary, 2022). This study's research hypotheses were evaluated using the AMOS version 23.…”
Section: Direct Hypotheses Testingmentioning
confidence: 99%
“…Different analytical tools and applications were used to code the data and extract knowledge (Tables 2 and 3, Figures 3-5), including the correlation matrix, composite reliability, Cronbach's alpha, and bootstrapping. The variables were mined with Smart-PLS3 [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. After correlating data and variables and verifying the model's reliability, we designed three regression models assuming this hypothesis was not rejected.…”
Section: Hypothesis 3 (H3) Student Collaborative Work Is Bootstrapped By the Use Of Blockchain In He For A Massive Audience (V5);mentioning
confidence: 99%